2019
DOI: 10.1186/s13000-019-0788-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of pagetoid urothelial intraepithelial neoplasia extending to the vagina by cervical screening cytology: a case report with renewed immunochemical summary

Abstract: BackgroundPagetoid spread of urothelial carcinoma (UC) to the lower genital tract is quite a rare and diagnostically challenging condition. Pagetoid urothelial intraepithelial neoplasia extending to the vagina is difficult to diagnose, especially in remote recurrences without symptomatic or macroscopic lesions typical to Paget disease. However, its identification by cervical screening cytology is important because UC is often characterized by a long history of relapse.Case presentationA 68-year-old Japanese po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Padhy et al presented a case of secondary Paget disease of urothelial origin without previous or concurrent urinary tract malignancy. Urothelial origin was determined based on the immunohistochemical profile, with expression of GATA3, uroplakin III, and p63, similar to our case and to other authors [11,14]. In our case, the previous urothelial carcinoma was of low grade and had been under control for years.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Padhy et al presented a case of secondary Paget disease of urothelial origin without previous or concurrent urinary tract malignancy. Urothelial origin was determined based on the immunohistochemical profile, with expression of GATA3, uroplakin III, and p63, similar to our case and to other authors [11,14]. In our case, the previous urothelial carcinoma was of low grade and had been under control for years.…”
Section: Discussionsupporting
confidence: 74%
“…An interesting feature of the case reported here was the cervical involvement apparent on cervicovaginal cytology. Koyanagi et al presented a case of high grade urothelial carcinoma with pagetoid spread to the vagina, without accompanying Paget disease presentation [14]. The authors discuss the differences between pagetoid urothelial carcinoma, pagetoid colorectal carcinoma and extramammary Paget disease, highlighting the importance of cervical screening cytology.…”
Section: Discussionmentioning
confidence: 99%
“…Articles eligible for the study included primary studies that reported EMPD with abnormal cervical cytology. From these, we reviewed 10 articles describing 11 cases that matched the above ( Table 1 ) [ 3 – 12 ]. It should be noted that among the 12 cases, 6 were primary EMPD, 5 were secondary EMPD derived from urothelial carcinoma, and 1 was secondary EMPD derived from a rectal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary EMPD is subclassified into type I (secondary to anorectal or urothelial neoplasia) and type II (Paget disease secondary to adenocarcinomas or related tumors of other sites) [ 1 ]. There are reports of vulvar primary EMPD and secondary EMPD derived from the bladder or rectum spreading to the cervix through the epithelium, but only 11 cases of vulvar EMPD with abnormal cervical cytology have been reported in the English literature [ 3 – 12 ]. Herein, we present a case of type I secondary EMPD derived from urothelial carcinoma diagnosed after cytological examination for cervical cancer screening.…”
Section: Introductionmentioning
confidence: 99%
“…However, cases of secondary EMPD developed from urothelial carcinoma showing negative CK20 staining have also been reported [42], suggesting that the combination of CK7/CK20 staining is not an absolute method to discriminate primary from secondary EMPD. As for other markers, CDX-2, an intestinal cell marker, and uroplakin II and III, urothelial cell markers, could be also useful for the discrimination: both are usually negative for primary EMPD [40,[43][44][45]. Collectively, comprehensive evaluation using multiple markers, including CK7/20, GCDFP-15, CDX-2, and uroplakin II and III, is required for accurate discrimination of primary EMPD and secondary EMPD.…”
Section: Histopathologymentioning
confidence: 99%